The regulatory role of APE1 in epithelial‐to‐mesenchymal transition and in determining EGFR‐TKI responsiveness in non‐small‐cell lung cancer. (14th August 2018) - Yang, Xiao; Peng, Yu; Jiang, Xuan; Lu, Xianfeng; Duan, Wei; Zhang, Shiheng; Dai, Nan; Shan, Jinlu; Feng, Yan; Li, Xuemei; Cheng, Yi; Yang, Yuxin; et al.
Abstract: Background: Epithelial‐to‐mesenchymal transition (EMT) plays a pivotal role in resistance to EGFR tyrosine kinase inhibitors (TKIs) in non‐small‐cell lung cancer (NSCLC). Our previous study revealed that in osteosarcoma, human apurinic/apyrimidinic endonuclease 1 (APE1) regulates transforming growth factor‐β (TGF‐β), an important player in EMT. We therefore hypothesized a link between APE1 and EGFR‐TKI responsiveness in NSCLC. Methods: The protein levels of APE1 were analyzed in tumors of NSCLC patients receiving EGFR‐TKI treatment. The correlation between APE1 expression and progression‐free survival (PFS), overall survival (OS), or response rate were analyzed. The impact of APE1 on the response to EGFR‐TKIs was measured by exogenous manipulation of APE1 in EGFR‐TKI‐sensitive and EGFR‐TKI‐resistant cells. Results: We indicate that low expression of APE1 in tumors is associated with a significantly longer PFS (20.8 months vs 8.4 months, P  =   0.008) and a preferential OS (39.0 months vs 17.0 months, P  =   0.001), with no difference in initial response rate to EGFR‐TKIs. We observed that APE1 protein level was significantly increased in EGFR‐TKI‐resistant cells and was associated with downregulated E‐cadherin and upregulated vimentin. The EMT phenotype, as well as the levels of TGF‐β, was suppressed in APE1 knockdown HCC827/IR and PC‐9/ER cells, while the EMT phenotype was promoted in APE1‐overexpressed HCC827 and PC‐9 cells. Furthermore, a specific APE1 redox inhibitor (ie, E3330) effectively reversed the EMT phenotype and further sensitized the cells to EGFR‐TKIs. Conclusion: This study revealed a significant role of APE1 in EGFR‐TKI resistance via novel regulatory effects on the EMT phenotype in NSCLC. Abstract : APE1 level is correlated with poorer therapeutic outcomes of EGFR‐TKI treatment. APE1 determines EGR‐TKI response by promoting epithelial–mesenchymal transition. Inhibition of APE1 activity reverses the resistance to EGFR‐TKI.